Review Paper: Coding Systems in Health Care - Cimino, J. J. (Methods of Information in Medicine, 1996)
Computer-based patient data which are represented in a coded form have a variety of uses, including direct patient care, statistical reporting, automated decision support, and clinical research. No standard exists which supports all of these functions. Abstracting coding systems, such as ICD, CPT, DRGs and MeSH fail to provide adequate detail, forcing application developers to create their own coding schemes for systems. Some of these schemes have been put forward as possible standards, but they have not been widely accepted. This paper reviews existing schemes used for abstracting, electronic record systems, and comprehensive coding. It also discusses the remaining impediments to acceptance of standards and the current efforts to overcome them, including SNOMED, the Gabrieli Medical Nomenclature, the Read Clinical Codes, GALEN, and the Unified Medical Language System (UMLS).
Keywords: Controlled Medical Vocabulary; Nomenclature; Taxonomy; Electronic Medical Records; Medical Record Coding; Review